2021
DOI: 10.37190/ppmp/132779
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometallurgical recovery of platinum group metals from spent automotive converters

Abstract: This work presents studies on the recovery of platinum group metals (PGM), especially platinum and rhodium, from spent automotive converters using hydrometallurgical techniques such as leaching and liquid-liquid extraction. The XRD analysis confirmed the presence of indialite -the hightemperature hexagonal form of cordierite (the main catalyst building material) in the solid samples. The influence of time and temperature on the leaching of PGM from spent automotive converters was investigated. The largest amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…These ILs have a higher affinity towards Pt, Fe, and Zn, which likely form anionic chloro-complexes in the chloride media, while they have a low affinity for La, Mg, and Al which are bare cations. A similar extraction selectivity of ILs to these metals from SAC leaching solutions was reported in the literature [20][21][22][23]. Therefore, it was indicated that the leaching selectivity for ILs observed in Figure 1 followed the affinity of the leached metals for ILs.…”
Section: Direct Leaching Of a Spent Automotive Catalyst By Ilssupporting
confidence: 85%
“…These ILs have a higher affinity towards Pt, Fe, and Zn, which likely form anionic chloro-complexes in the chloride media, while they have a low affinity for La, Mg, and Al which are bare cations. A similar extraction selectivity of ILs to these metals from SAC leaching solutions was reported in the literature [20][21][22][23]. Therefore, it was indicated that the leaching selectivity for ILs observed in Figure 1 followed the affinity of the leached metals for ILs.…”
Section: Direct Leaching Of a Spent Automotive Catalyst By Ilssupporting
confidence: 85%
“…5,6 Another route consists of the electrochemical dissolution of platinum nanoparticles into Pt(II) in acidic media. 7,8 Few reports have depicted the direct extraction of platinum in its metallic form from the different components of the catalytic layer. To our knowledge, only three patents more focused on ionomer recovery described the concomitant recovery of the platinum metal.…”
Section: Introductionmentioning
confidence: 99%
“…The ashes resulting from the combustion are processed by dissolving them in a mixture of strong acids (aqua regia) . Finally, the soluble platinum is recovered by separation, precipitation, and solvent extraction (liquid–liquid extraction). , Another route consists of the electrochemical dissolution of platinum nanoparticles into Pt­(II) in acidic media. , …”
Section: Introductionmentioning
confidence: 99%
“…Pt/Al 2 O 3 catalysts are widely used in the chemical industry. After being used for a certain amount of time, the catalytic performance of the catalysts will evidently be decreased and spent Pt/Al 2 O 3 catalysts will be produced [6][7][8][9]. The spent Pt/Al 2 O 3 catalysts have very high economic value.…”
Section: Introductionmentioning
confidence: 99%